How can i simplify this function?

Status
Not open for further replies.

life24

Newbie level 6 Hi,
(A+B) XOR A
and
(A' + B) XOR A
And explain this. thank you

TSS1990

Newbie level 3 (a+b)xor a = (a+b)a'+(a+b)'a = ba'+a'b'a = ba'

(a'+b)xor a = (a'+b)a'+(a'+b)'a = (a'+ba')+ab'a = a'+ab'
= a'+b'

Last edited:

life24

Newbie level 6 (a+b)xor a = (a+b)a'+(a+b)'a = ba'+a'b'a = ba'

(a'+b)xor a = (a'+b)a'+(a'+b)'a = (a'+ba')+ab'a = a'+ab'
= a'+b'

Thank you,
Do these two is equivalent? and - - - Updated - - -

Hi,
Can you simlify this? thanks TSS1990

Newbie level 3 No, they are not.

life24

Newbie level 6 Super Moderator
Staff member Can you simlify this? thanks
View attachment 104495
Yes I could, but that won't help you learn Boolean algebra, and defeats the purpose of you having homework problems that you need to solve.

Regards

life24

Newbie level 6 Yes I could, but that won't help you learn Boolean algebra, and defeats the purpose of you having homework problems that you need to solve.

Regards
Hi,
No this is not my homework.
This ambiguity is a test Super Moderator
Staff member Well if it's for a test to...
a) get a grade in a class
b) get a job

Then that is even worse than if it was homework.
a) you get a good grade and didn't actually do the work and didn't know how to derive the answer yourself.
b) got the job and aren't qualified to do the work they hire you to do.

life24

Newbie level 6 Well if it's for a test to...
a) get a grade in a class
b) get a job

Then that is even worse than if it was homework.
a) you get a good grade and didn't actually do the work and didn't know how to derive the answer yourself.
b) got the job and aren't qualified to do the work they hire you to do.

I'm not a liar.This is not my homework.

Super Moderator
Staff member Here are some Boolean operations that are needed to solve this problem

a'a = 0
b(c + d) = bc + bd
which allows you to derive the following if you make b = (e + f):
(e + f)(g + h) = eg + eh + fg + fh

Regards

rca well in all case, like ads-ee, I think you spend more time to write the ticket in edaboard instead solving this boolean equation, if not, you have a problem to be a electronic technician (at least).

Status
Not open for further replies.